Assessment of Professional Development by Teachers and Administrators: An examination of the literature in the context of one case study - Hinds, Marjorie; Berger, Marie (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2010)
The focus of this article is teacher professional development. The article examines literature related to teacher professional development and methods of measuring its impact. In order to ground the discussion, the article focuses on a case study that captures the perspectives of Ontario secondary school teachers and their administrators as they implement a literacy program targeted at improving student achievement.